Characterization of a novel freshwater gigartinalean red alga from Belize, with a description of Sterrocladia belizeana sp nov (Rhodophyta) - Sherwood, Alison R.; Necchi, Orlando [UNESP]; Carlile, Amy L.; Laughinghouse, H. Dail; Fredericq, Suzanne; Sheath, Robert G. (Int Phycological Soc, 2012)
Freshwater representatives of the red algal order Gigartinales are extremely rare, with the monotypic genus Sterrocladia being the only truly freshwater example. This alga was described in 1850 from material originating from French Guiana, and although its affinities at the ordinal and familial levels have been debated based on morphological and anatomical characteristics, its placement has not been confirmed with the assistance of molecular analyses. Here we report several collections of a freshwater red alga from Belize that share many of the characteristics of the single described species, Sterrocladia amnica, but also display some important differences. Based on microscopic analysis, our collections were distinguished from S. amnica based on thickness of the cortical layer, cell size, possession of a loose versus entire medulla and absence of reproductive nemathecia. Transmission electron microscopy confirmed a pit plug anatomy consistent with placement of the new collections in the order Gigartinales, and a new method for resin infiltration into thick cortical tissue was described. Although recent material of S. amnica was unavailable, molecular phylogenetic analyses of the rbcL and SSU rRNA gene for our new samples indicated that it was indeed a member of the Gigartinales, and that it was positioned basal to the Gigartinaceae and Phyllophoraceae clades, likely representing a novel family. The COI-5P barcode sequence showed no close matches, but the vast majority of the closest hits were to representatives of the Phyllophoraceae. Here we describe a second species within the genus Sterrocladia to accommodate our Belizean collections, Sterrocladia belizeana sp. nov., and discuss the phylogenetic affinities of this unique genus of freshwater gigartinalean red algae. We also propose a lectotype of Sterrocladia amnica based on examination of syntype materials.
Keywords: Belize; Fresh water; Gigartinales; Phylogeny; Rhodophyta; Sterrocladia belizeana; Transmission electron microscopy